the effect of Kegel Exercise toward urinary in continence on the elderlies - Novera, Milya (LLDIKTI Wilayah X, 2017)
Because of the increasing age, it causes the changes of anatomy and function of the urinary organs caused by weakening of the pelvic muscles. About 12 million people, 34% occurred in men and 60% in women. Indonesia 32.2% in the Elderlies suffers urinary incontinence. The aims of this study was to determine the effect of Kegel Exercise toward urinary in continence on the elderlies.The design of this study is Quasy experiment with design of one group pretest-posttest. This research was conducted in January-August 2015. The population in this research was 110 Elderlies, based on inclusion criteria were 12 people taken by total sampling techniques. The Data was collected by using questionaire and checklist sheets. Data were analyzed by using univariate and bivariate statistical dependent T-test with Shapiro Wilk normality test. The result showed that the frequency of urinary incontinence in the elderlies before doing Kegel exercises had the average about 10.58 with deviation 2,065. Freqency of urinary incontinence in the elderlies after doing Kegel exercises had the average about 8.00 with standard deviation 2,796. After doing the statistical, there is the effect of urinary incontinence before and after doing Kegel exercises in the elderlies. Kegel exercises can reduce urinary incontinence. It can be applied as the daily activities at social institution every day.